Synthesis of FeNi3/SiO2/CuS magnetic nano-composite as a novel adsorbent for Congo Red dye removal. Issue 10 (9th August 2022) - Nasseh, Negin; Arghavan, Fatemeh Sadat; Rodriguez-Couto, Susana; Hossein Panahi, Ayat
ABSTRACT: In the present study the magnetic nanocomposite FeNi3 /SiO2 /CuS was synthesised to be applied as a dye adsorbent. The synthesised nanocomposite was characterised using Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM), Vibrating Sampling Magnetometry (VSM) and X-ray Diffraction (XRD). Further, the efficiency of the synthesised nanocomposite was applied as an adsorbent for the removal of the dye Congo Red (CR) from aqueous solutions. The effect of different variables, including pH, contact time, adsorbent dosage, initial CR concentration and temperature, on CR adsorption was evaluated. A maximum CR adsorption of 100% after 200 min was found when operating at an adsorbent concentration of 2 g/L, a pH of 5, an initial CR concentration of 30 mg/L and a temperature of 25°C. CR adsorption followed a pseudo-second-order kinetic model. In addition, the equilibrium data fitted the Langmuir isotherm. Overall, the obtained results indicated that the synthesised nanoparticles can be used as an effective adsorbent in dye removal.